Karakteristik Sifat Kimia Tanah Lahan Jagung Jenis Tanah Berbeda di Desa Unit Pemukiman Wuna Kecamatan Tongkuno - Hasnawati, Andi; Ginting, Sahta; Resman, Resman; Darwis, Darwis; Alam, Syamsu; Namriah, Namriah (CV. Eduartpia Publisher, 2024)
Different soil types have varying soil fertility potentials, which contribute to the crop yields obtained. The aim of this study is to analyze the characteristics of soil pH, organic carbon (C-Organic), and cation exchange capacity (CEC) and to determine appropriate management practices for corn cultivation on two different soil types in Unit Pemukiman Wuna Village, Tongkuno District. The method used in this study was a free survey method utilizing minipits for each soil type. Soil sampling was conducted using a composite method, where soil samples were taken from three points for each soil type at depths of 0–30 cm (topsoil) and 30–60 cm (subsoil). The soil from each layer was then composited, and approximately ±1 kg of soil was taken for laboratory analysis to determine its pH, Organic-C, and CEC levels. The results showed that the chemical properties of soil type 1 (Alfisol) had a lower pH than soil type 2 (Mollisol), with values of 5.02 and 5.24, respectively. Similarly, the CEC analysis indicated that soil type 1 had a lower CEC compared to soil type 2, with values of 5.16 and 5.20 me/100 g, respectively. However, in terms of soil organic carbon content, the analysis revealed that the Organic-C level in Alfisol was higher than in Mollisol, with values of 5.66% and 3.47%, respectively. Appropriate management practices for corn cultivation require efforts to increase soil pH and CEC through liming and zeolite application. Additionally, to maintain pH, C-Organic, and CEC levels, blanket herbicide application should be avoided, and excessive use of chemical fertilizers should be minimized to sustain soil health and land sustainability